Two new species of Solenysa Simon, 1894 (Araneae: Linyphiidae) from Japan - Tu, Lihong; Ono, Hirotsugu; Li, Shuqiang (Zootaxa, 2007)
Two new species of Solenysa Simon, 1894 from Japan are described, i. e. Solenysa reflexilis sp. nov. and Solenysa partibilis sp. nov. The differences of the genitalic structures between both new species and related species are studied.